Socio- organizational reading of the relationship between organizational loyalty and employee satisfaction - kadja, redha; khiri, asma (Journal of Social Sciences and Humanities, 2020)
The success, effectiveness and efficiency of an organization depend on the willingness of workers to work effectively and accurately, and the effectiveness of these depends not only on their training and development, but also on the degree of loyalty and satisfaction of these workers to the organization. Therefore, in modern organizations, the administration strives to retain workers by increasing their level of job satisfaction by adopting strategies to meet their needs, which generates a sense of belonging and increased morale, as well as the motivation of the workers to work and the stability of the organization and their reluctance to leave their jobs. The subject of loyalty is one of the most important topics in the field of administration and its functions. This can be seen as one of the organizational variables that havea significant impact on the work efficiency, the behavior and motivation of workers towards work, their colleagues and the company in which they work.Therefore, the effective role of organizational loyalty appears in terms of influencing the organizational and orientation behavior of the worker within the organization, which contributes to improving job satisfaction and reducing negative behaviors. which contributes to achieving the objectives of the institution. In this article, we will try to treat the organizational loyalty variable by clarifying its concept, its dimensions, its characteristics, its development factors and its relation to the job satisfaction of the worker in the organization in which he works. explaining the reasons for his interest in job satisfaction, its importance and the factors that affect it.